O ensino de Filosofia e a experiência filosófica no Centro de Educação de Jovens e Adultos (CEJA) - Chagas, Divina Mendes (2021)
The question that gave rise to this research was: how to teach Philosophy to students at the Youth and Adult Education Center (CEJA)? The initial answers led me to the concept of experience and made me notice its relevance for thinking about the teaching of Philosophy in this modality of Basic Education. The research project arises from the classroom experience and returns to it. The dynamics in which the writing of the chapters moves is that of the patchwork, I start to sew questions, possibilities and authors. In this sense, a brief history of Adult Education was traced with reference to the Unesco International Conferences (2012), but also the studies of Andragogy of Knowles (2015) and adult education present in the works of Paulo Freire (1996). I briefly investigate the history of CEJA in the State of Mato Grosso and the Philosophy documented at BNCC. Next, a brief history of the concept of experience in the History of Philosophy is presented, with a view to building a creative appropriation of the works of Gelamo (2006), Aspis (2012) and Deleuze (2010); I continue with the characterization of the philosophical experience and conclude with its support through philosophical reading and writing. In the sequence, the differences that may exist between teaching, communicating and philosophizing are highlighted; to defend the teaching of Philosophy as a philosophical experience, and Rancière (2002) was the author who helped me at this time. Finally, I present a proposal for a philosophical intervention in the classroom, supported by excerpts from the work of Frantz Fanon (2008) and the methodology proposed by Silvio Gallo (2012).